Linear verrucous haemangioma--a rare case and dermoscopic clues to diagnosis - Dhanta, Aditi; Chauhan, Payal; Meena, Dilip; Hazarika, Neirita (Dermatology Practical & Conceptual, 2018)
Verrucous hemangioma (VH) is a rare, congenital and localized vascular malformation, which usually presents as warty, bluish, vascular papules, plaques, or nodules, mainly on the lower extremities. Linear presentation of the disease is rare. A deep biopsy is necessary to confirm the clinical diagnosis by histopathological examination, with dermoscopy acting as a useful tool for evaluating the precise vascular structure. Here, we report on a 13-year-old female child with linear VH presenting over her foot since infancy and dermoscopic findings of VH along with the clinical-pathologic features.